RANCANG BANGUN SISTEM INFORMASI REKAM MEDIS BERBASIS WEB PADA PRAKTEK UMUM DR. A. ESTI JAKARTA - Rudianto, Rudianto; Cahyaningtyas, Zefanya Desy (Aksara Public, 2018)
General practice Dr. A. Esti is a health service facility located in West Jakarta. Common practice commonly known as Dr. A. Esti provides health services such as consultations, health checks and medical treatment in general. In general practice Dr. A. Esti where the author researches the system of data recording and storing is still using the manual method by using books and papers to recap patient data, patient medical record data, and visit data. This is very inefficient, because if the patient checks again the staff will find it so difficult to find medical records of patients who have previously conducted an examination. Making this system uses system development methods, namely the waterfall model method. The proven waterfall method can be used to design a system well starting from system requirements analysis, design, code generation, testing, and support. The system is also described using Unifield Modeling Language (UML). This system is web based, the programming language used is PHP, Javascript, and CSS. Design Of Web-Based Medical Record Information System is a system that regulates and manages all patient data, helps officers, doctors and owner to manage all data in General Practice Dr. A. Esti.